2015
DOI: 10.1111/pme.12864
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the Screener and Opioid Assessment for Patients with Pain-Revised (SOAPP-R): A Proof-of-Principle Study for Customized Computer-Based Testing

Abstract: Background The Screener and Opioid Assessment for Patients with Pain-Revised (SOAPP-R) is a 24-item self-report instrument that was developed to aid providers in predicting aberrant medication-related behaviors among chronic pain patients. Although the SOAPP-R has garnered widespread use, certain patients may be dissuaded from taking it because of its length. Administrative barriers associated with lengthy questionnaires further limit its utility. Objective To investigate the extent to which two techniques f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 58 publications
2
25
1
Order By: Relevance
“…Recent research on the SOAPP-R has indicated an interest in and the feasibility of employing a computerized version of the screener 42,67. The regular use of a computer-based SOAPP-R would facilitate the collection of further response-time data, which would open the door to new methods of determining risk of ADB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the SOAPP-R has indicated an interest in and the feasibility of employing a computerized version of the screener 42,67. The regular use of a computer-based SOAPP-R would facilitate the collection of further response-time data, which would open the door to new methods of determining risk of ADB.…”
Section: Discussionmentioning
confidence: 99%
“…In stochastic curtailment, the screener is stopped at any stage of testing where curtailment would stop it, as well as at any stage of testing where the final result of the SOAPP‐R (“positive” or “negative”) is predicted with a high level of probability (such as 95% or 99%). In previous research conducted retrospectively, curtailment lowered the average test length of the SOAPP‐R by 26% without any change in sensitivity or specificity; stochastic curtailment lowered the average test length by up to 65% without changing the sensitivity or specificity by more than 3.5% (Finkelman et al., ).…”
Section: Introductionmentioning
confidence: 94%
“…Existing validated questionnaires are available to assist clinicians in screening patients for potential aberrant medication‐related behaviors, including the Opioid Risk Tool (Webster & Webster, ) and the Screener and Opioid Assessment for Patients with Pain‐Revised (SOAPP‐R; Butler, Budman, Fernandez, Fanciullo, & Jamison, ). The latter questionnaire has undergone validity testing (Butler, Fernandez, Benoit, Budman, & Jamison, ) and has been extensively researched in subsequent studies (Finkelman et al., , ; Finkelman, Jamison, et al., ; Finkelman, Smits, et al., ; Jones et al., ; Weiner, Horton, Green, & Butler, , ). The full‐length version of the SOAPP‐R consists of 24 self‐report items (whose item scores are summed to obtain a total score), with a single cutoff point to categorize patients as either low risk or high risk for aberrant medication‐related behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations